2020
DOI: 10.1080/00141844.2019.1687540
|View full text |Cite
|
Sign up to set email alerts
|

Eviction, Gatekeeping and Militant Care: Moral Economies of Housing in Austerity London

Abstract: This article uses the lens of moral economies to examine the everyday experience of eviction, precarious housing and grassroots activism in contemporary London. Situated within a context of ongoing austerity measures, it explores how divergent, conflicting and overlapping moral economies of housing emerge both within the state and at its margins, as local authorities struggle to reconcile contradictory obligations to both uphold property relations and offer a duty of care to tenants. The article shows how bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Similar to the housing officers studied by Wilde (2020) who justify 'gatekeeping' practices by referring to 'a desire to be fair in a context of scarce resources' (see also Alden, 2015), frontline workers spoke of how they made the most of a tough situation where resources were limited by helping those who 'want to be helped', and who can be 'empowered'. But what was presented as a necessary, morally justified form of crisis management also constituted what Higgins (1980) called a form of social control.…”
Section: Model Customers and Their Counterparts: Allocating Scarce Rementioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the housing officers studied by Wilde (2020) who justify 'gatekeeping' practices by referring to 'a desire to be fair in a context of scarce resources' (see also Alden, 2015), frontline workers spoke of how they made the most of a tough situation where resources were limited by helping those who 'want to be helped', and who can be 'empowered'. But what was presented as a necessary, morally justified form of crisis management also constituted what Higgins (1980) called a form of social control.…”
Section: Model Customers and Their Counterparts: Allocating Scarce Rementioning
confidence: 99%
“…Here, I follow Palomera and Vetta in their political economy-driven reading of moral economy and its recent application to discussions of austerity and inequality (Alexander et al, 2018; Pusceddu, 2020; Wilde, 2020). Like the grain studied by Thompson, access to welfare services and advice is essential to the daily survival of today’s most marginalised populations.…”
Section: The Moral Economy Of Frontline Work: Conceptualising the Ethmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that ‘interlinked shifts’ in capital accumulation and state policy together generate insecurity in housing tenure (Wilde in press). These shifts include: liberal policies that favour the interests of landlords and lenders, including by removing rent controls and barriers to eviction (Gutierrez‐Garza in press; Wilde in press); austerity; the securitization of mortgages (Sabaté ) and capital's increased reliance on financial extraction generally (Suarez ); models for economic growth reliant on property prices (Dorling ); subsidies for home‐ownership (Palomera ); de‐industrialization causing wage stagnation and volatility (Desmond ); and urban redevelopment and compulsory purchase orders (Ho ; Lewis ). I build on this research by arguing that liberalization is a process whereby the discretion to adjudicate on legally enforceable intrusions into the home is distributed among state and market agencies such as landlords, lenders, and bailiffs (also known as ‘enforcement agents’).…”
mentioning
confidence: 99%
“…But the state's involvement in ordinary homes can go further than contributing to their precarity. Research on housing activism has shown counter‐hegemonic moral economies forming in response to possible dispossession (Gutierrez‐Garza in press; Sabaté ; ; Suarez ; Wilde in press). Comparable moral reasoning also arises online (Stout ).…”
mentioning
confidence: 99%